Adolescent Behavior in Implementing Clean and Healthy Living Practices through Local Wisdom-Based Character Education: A Cross-Sectional Study - Ahmad Yani; Indra Afrianto; Muhammad Syukran; Wa Ode Nova Noviyanti Rachman; Zuriati Muhamad (Journal of Public Health and Pharmacy, 2025)
Introduction: Adolescence is a crucial phase for the development of lifelong health behaviours. Clean and Healthy Living Behavior (PHBS) is essential for enhancing public health, particularly among adolescents. This study focuses on the role of character education based on local wisdom in promoting PHBS among adolescents in Balaesang District, Donggala Regency. Methods: A cross-sectional study was conducted from June to September 2024, involving 150 adolescents aged 12-15 years. Data were collected using structured questionnaires and field observations. The study evaluated the relationship between knowledge, attitudes, and actions towards PHBS and the impact of character education based on local wisdom. Data analysis was conducted using the chi-square test. Results: The findings revealed significant relationships between knowledge (p = 0.004), attitudes (p = 0.001), and actions (p = 0.002) toward the implementation of PHBS. Character education based on local wisdom was found to strengthen adolescents' knowledge, attitudes, and actions, leading to improved implementation of PHBS. Conclusion: Character education incorporating local wisdom plays a vital role in promoting clean and healthy behaviours among adolescents. Integrating cultural values with health education can effectively enhance the knowledge, attitudes, and actions of students, contributing to better public health outcomes.